Comparative Evaluation of GBR Techniques Using Zirconia Barrier Membrane: An In-vivo Study - Zeynep Tuncludemir (Medicine and Medical Research: New Perspectives Vol. 7, 2024)
Aims: This study aims to evaluate the effects of customized zirconia barrier membranes produced for guided bone regeneration approaches on bone healing researched with histological and histomorphometric methods. Study Design: In vivo experimental study. Place and Duration of Study: The digital modeling and writing phase took place at Istanbul University Faculty of Dentistry, Department of Oral Implantology. The surgeries and sacrification procedures for the experimental animals were carried out in the operating rooms of the Surgery Department at the Faculty of Veterinary Medicine, Bursa Uludag University. The bone tissue samples obtained were histologically and histomorphometrically evaluated in the laboratories of the Pathology Department at the same university. The study started in August 2022 and ended in February 2024. Methodology: The research involved using digital modeling to create zirconia barrier membranes suitable for a defect in the tibia bone. These membranes were designed using a 3D software system and transferred to the CAD/CAM software system in STL format. Zirconia discs (1400 Mpa) (Aconia BSM- D98x16, HT+, Germany) were then milled and sintered. The defects were covered using titanium mesh, titanium-reinforced d-PTFE, and zirconia barrier membranes, while one defect was left empty for the control group. At 3 and 6 weeks into the healing period, samples were obtained from each group after sacrificing the animals. Histomorphometric and histological analyses were conducted to evaluate new bone formation, the amount of remaining grafts, and tissue response parameters. Results: The newly formed bone amounts of the zirconia barrier membrane, titanium membrane, and d-PTFE membrane groups were significantly higher than the control group in the 3rd and 6th weeks. The amount of residual graft progressed at a low level in both periods without any difference in the other groups except the control group. No foreign body reaction or necrosis was observed in any of the defects. Conclusion: With the limitation of the study, it has been concluded that effective results can be obtained with zirconia barrier membranes in GBR procedures.